A Rare Case of Aluminum Phosphide Induced Thrombotic Thrombocytopenic Purpura - Nafiseh Alizadeh; Mina Borran; Behnam Behnoosh; Mehrnoush Dianatkhah (Research Center for Rational Use of Drugs (RCRUD), 2021)
Aluminum phosphide (AlP) has remained a chemical cause of completed suicides in some developing countries. ALP toxicity can cause multi-system damage. As far as we know, this is the first case of ALP-induced Thrombotic Thrombocytopenic Purpura (TTP) and its successful management. A 34-year-old man, who had attempted suicide with ALP was admitted to our hospital. On the 3rd day of admission, the patient developed hematuria, hemolysis, and thrombocytopenia. Based upon available evidence, TTP was diagnosed. Following a complete patient evaluation, ALP was recognized as the probable cause of TTP. Following the treatment using prednisolone and therapeutic plasma exchange, the patient substantially improved. Finally, he was discharged on the 22nd day. Toxin-induced intravascular hemolysis should be considered for patients presenting with ALP toxicity. As reported in this patient, TTP is another manageable consequence of ALP poisoning.